Salvage Magnetic Resonance Imaging–guided Transurethral Ultrasound Ablation for Localized Radiorecurrent Prostate Cancer - Anttinen, Mikael; Mäkelä, Pietari; Nurminen, Pertti; Pärssinen, Heikki; Malaspina, Simona; Sainio, Teija; Högerman, Mikael; Taimen, Pekka; Blanco Sequeiros, Roberto; Boström, Peter J. (Elsevier, 2025)
Background and objective: Toxicity from local salvage therapy for radiorecurrent prostate cancer (PCa) remains a concern. This phase 2 study evaluates the outcomes of salvage magnetic resonance imaging (MRI)-guided transurethral ultrasound ablation (sTULSA).
Methods: Men with biochemically relapsed, biopsy-proven PCa following definitive radiotherapy underwent whole- or partial-gland sTULSA (NCT03350529). Prostate-confined recurrence was confirmed by MRI and prostate-specific membrane antigen (PSMA) positron emission tomography (PET) computed tomography (CT). The primary endpoints were safety (Clavien-Dindo classification) and efficacy (prostate-specific antigen [PSA], PSMA PET-CT, and MRI-targeted biopsy at 12 mo). The secondary endpoints included functional and survival outcomes.
Key findings and limitations: Thirty-nine patients underwent sTULSA (64% whole gland), with a median age of 73 yr (interquartile range [IQR]: 69–77) and PSA of 3.3 ng/ml (IQR: 2–6.2). Three patients had undergone prior salvage therapy, 16 were receiving hormonal therapy at enrollment, and 12 had a history of transurethral interventions. Eighteen patients had incidental urethral strictures on baseline cystoscopy. Over a median follow-up of 40 mo (IQR: 24–55), 56% experienced adverse events. Severe genitourinary toxicity (Clavien-Dindo ≥3 or hospitalization) occurred in 28%, including three patients with puboprostatic fistulas and two patients requiring cystectomy. Leak-free continence was maintained in 53%. At 12 mo, 89% showed no cancer in the targeted area, with a median PSA reduction of 95% (p < 0.001). Five-year metastasis-free, failure-free, and biochemical recurrence–free survival probabilities (95% confidence interval) were 97% (0.93–1.00), 70% (0.54–0.91), and 54% (0.31–0.93), respectively. Limitations included single-arm design and moderate sample size.
Conclusions and clinical implications: It has been observed that sTULSA is effective for radiorecurrent PCa, although genitourinary toxicity remains a concern. Further studies should refine patient selection and treatment parameters to improve safety and tolerability.
Patient summary: In this study, we examined a new treatment called magnetic resonance imaging–guided transurethral ultrasound ablation for prostate cancer that has returned after radiation therapy. We found that the treatment provided effective and lasting cancer control for most patients. However, a notable number of patients experienced significant genitourinary toxicity, including severe adverse effects affecting urinary function. Careful patient selection is crucial to minimize these adverse effects and ensure the best results.